An evaluation of POSSUM and P-POSSUM scoring in predicting post-operative mortality in a level 1 critical care setting - Scott, Sarah; Lund, Jonathan N.; Gold, Stuart; Elliott, Richard; Vater, Mair; Chakrabarty, Mallicka P.; Heinink, Thomas P.; Williams, John P. (BioMed Central, 2014)
Background